The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s00405-022-07320-y
|View full text |Cite
|
Sign up to set email alerts
|

BMI as a risk factor for the development of chronic rhinosinusitis: a prospective population-based study

Abstract: Purpose Obesity is a growing, global health problem and previous cross-sectional studies have demonstrated an association between obesity and chronic rhinosinusitis (CRS). There is, however, a lack of prospective studies regarding the impact of obesity on developing (new-onset) CRS. Methods Questionnaire-based data (n = 5769) relating to new-onset CRS and Body Mass Index (BMI) were collected in 2013 and 2018 from the Telemark population study in Telemark, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 42 publications
(49 reference statements)
1
6
1
Order By: Relevance
“…An association between BMI or its categories and sinusitis was hereby established, which was consistent with several previous studies [9,17,18]. Although the clinical characteristics of the study populations, the types of olfactory assessment tests varied substantially by report.…”
Section: Discussionsupporting
confidence: 89%
“…An association between BMI or its categories and sinusitis was hereby established, which was consistent with several previous studies [9,17,18]. Although the clinical characteristics of the study populations, the types of olfactory assessment tests varied substantially by report.…”
Section: Discussionsupporting
confidence: 89%
“…A cross-sectional analysis of 229 million U.S. adults revealed the association between the increase in BMI and the increased incidence of CRS [ 9 ]. A prospective population-based study demonstrated that the incidence of new CRS was 53% higher in the obese group (BMI ≥ 30) than in the normal weight group (18.5 ≤ BMI < 25) in the Norwegian population, and higher BMI was associated with an increased risk of CRS [ 40 ]. Our study also suggested that BMI had a causal effect on CRS.…”
Section: Discussionmentioning
confidence: 99%
“…Third, there was variability in the definition of CRS utilized between each study. For the Meta‐analysis on the odds of having CRS in the presence of obesity, CRS was defined by the validated EPOS2012 guidelines for epidemiological studies with sinus endoscopy, ICD‐9 codes (US‐based study), the EPOS2012 guidelines for epidemiological studies only, or radiologic findings only 12,15,16,21 . The variation of the CRS definition used between the studies may limit the power of the statistical association observed in this outcome due to misclassification bias.…”
Section: Discussionmentioning
confidence: 99%
“…For the Meta-analysis on the odds of having CRS in the presence of obesity, CRS was defined by the validated EPOS2012 guidelines for epidemiological studies with sinus endoscopy, ICD-9 codes (US-based study), the EPOS2012 guidelines for epidemiological studies only, or radiologic findings only. 12,15,16,21 The variation of the CRS definition used between the studies may limit the power of the statistical association observed in this outcome due to misclassification bias. Nonetheless, nearly every article included in this review uses a validated symptomatic diagnosis of CRS, 65 ICD codes, or a combination of sinonasal symptoms and radiologic evidence for the diagnosis of CRS, potentially minimizing the risk of misclassification.…”
Section: Limitationsmentioning
confidence: 99%